(untitled) - Krashen, Stephen D. (Westport, Conn, 2004)
Krashen also explores research surrounding the role of school and public libraries and the research indicating the necessity of a print-rich environment that provides light reading (comics, teen romances, magazines) as well as the best in literature to assist in educating children to read with understanding and in second language acquisition. He looks at the research surrounding reading incentive/rewards programs and specifically at the research on AR (Accelerated Reader) and other electronic reading products.
Keywords: Trình độ học vấn,Books and reading,Literacy,Sách và đọc sách